Study of Natural Nonionic and Cationic Surfactants Interactions in the Presence of Divalent Ions and their Effects on Enhancing Oil Recovery - Saniee, Mohammad Reza; Amir hosein Saeedi Dehaghani; Alavi, Seyed Ataollah (Journal of petroleum science and technology, 2024)
Although water and gas injection within enhanced oil recovery has garnered considerable attention in the contemporary era, some engineers argue that alternative and cost-effective methods could play a pivotal role in this field. The utilization of substances like surfactants and polymers is seen as an innovative technique that has substantially impacted the oil sector; however, the large-scale production of such materials is financially burdensome. Furthermore, manufacturing these substances results in hazardous wastes, posing risks to both human health and the environment, ultimately leading to extensive and irreversible pollution. Adopting natural surfactants emerges as a viable solution with relatively high efficacy. These plant-derived surfactants, extracted from indigenous plant leaves, are cost-effective, biodegradable, and pose no threat to human health or the environment. Incorporating these natural surfactants in oil-related experiments has yielded satisfactory outcomes, showcasing their effectiveness in reducing the interfacial tension between water and oil, modifying crude oil viscosity, and isolating heavy components of crude oil. Using conventional methods in the industry, such as water and gas injection, only leads to small exploitations, and in general, a considerable amount of oil remains in place. However, using modern methods, such as surfactant injection, these efficiencies increase to 30-40%. According to the micromodel injection tests, maximum recovery factors are achieved when natural surfactants interact well with divalent ions; the cedar non-ionic and Rosemary cationic surfactants have improved efficiency by 33% and 46%, respectively.